Representations of the Ideological Identity of Woman Characteristics in Commercial Advertisements - A.A. Sagung Diah Oka Yuniantari; I Wayan Budiarta; I Gusti Ayu Agung Dian Susanthi (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2021)
Commercial advertisement is a form of communication with the intention of promoting the sale of a particular product attached to a brand. The main strength of advertisement lies in the language and word choice (verbal signs), images (visual signs) as well as their creativity which is made as attractive as possible and followed by trends or phenomena that exist in the world, one of them is a gender issue. In commercial ads, woman is often shown referring to certain stereotypes so this research object is an advertisement that features woman as the main model. This research is focused on how advertising creates meanings regarding gender issues, especially for women through myth and ideology. Specifically, this research aims to describe the signs found in ads, the meaning of the signs, and ideological identity of the woman. The theory used in this research is the theory of semiotic by Roland Barthes (1991) and the theory of ideology by John Storey (2004). The data source of this research is commercial advertisements that have been shown on television. In collecting the data, the writer used the documentation method, observation method, and note taking technique. The collected data are classified based on their verbal and visual signs first. Then the data were analyzed based on denotative meaning, connotative meaning, myth, and representations of the ideological identity of woman produced by signs. The results of the analysis were presented by using formal and informal methods. Based on the results of the analysis, in Kondom Sutra ads there are two verbal signs in the form of dialog spoken by a woman and a man and there are six visual signs that produced denotative meaning and connotative meaning. The representation of ideological identity of woman that produced in this ads is, woman imagine as sensuality person. It shows from her sexy clothes, facial expressions like beating her lips and body curve that are able to arouse passion of the audiences.